Nutritional Rangers Mobile Application in Improving Child Nutrition, Feeding Response and Mother's Knowledge in Underprivileged Families - Reni Nurhidayah; Dhita Kurnia Sari; Prima Dewi Kusumawati (Journal Of Nursing Practice, 2024)
Background: Stunting is a major public health challenge, particularly in disadvantaged communities where access to adequate nutrition and healthcare is limited. Addressing this issue requires effective interventions to improve child nutrition and feeding practices. Objective: This study aims to evaluate the effectiveness of the Nutritional Rangers Mobile Application in improving child nutrition, feeding responses, and mothers' knowledge among underprivileged families with stunted children aged 6 to 24 months. Method: A pre-test and post-test design was employed, involving 22 mothers of stunted children from Kediri Regency, selected through purposive sampling. The app provided nutritional education, personalized dietary recommendations, and monitoring features over a three-month period. Results: Significant improvements were observed in child nutrition metrics, with mean weight increasing from 11.25 kg to 14.48 kg and height showing incremental growth. Paired sample t-tests confirmed statistical significance (p < 0.05) in all measured Z-scores (Weight-for-Age, Height-for-Age, and Weight-for-Height). Additionally, feeding responses and maternal nutritional knowledge significantly improved (p < 0.05). Discussion: The study highlights the effectiveness of the Nutritional Rangers Mobile Application in enhancing nutritional outcomes and maternal knowledge in resource-limited settings. The app's features contributed to significant improvements in child growth metrics and feeding practices. Conclusion: The Nutritional Rangers Mobile Application is a valuable tool for empowering mothers with nutritional education and real-time monitoring, leading to sustainable improvements in child health and nutrition outcomes in disadvantaged communities.